EVALUATION OF THE SUSTAINABILITY SHEEP DEVELOPMENT IN GALANG, DELI SERDANG DISTRICT - Galih Ari Wirawan Siregar; Teguh Azira Perkasa; Achmad Sadeli; Rizka Ramadhani (JURNAL NUKLEUS PETERNAKAN, 2026)
This study aims to evaluate the sustainability of sheep farming in Galang, Deli Serdang from March-May 2023. This study used the Multi-Dimensional Scaling (MDS) method with the Rap-Sheep approach for sustainability assessment. The sensitive attributes influencing the sustainability index and sustainability status were analyzed using Leverage analysis, whereas the effects of uncertainty and potential errors were examined using Monte Carlo analysis. The data used in the study included primary data and secondary data. Respondents used amounted to 90 sheep farmers. This study uses 4 dimensions, namely the ecological dimension with 12 attributes, the economic dimension with 10 attributes, the social dimension with 9 attributes, and the technology dimension with 10 attributes. The results showed that the sheep farming in Galang, Deli Serdang currently has a sustainability index value in the ecological dimension of 56,71 (quite sustainable), economic dimension of 51,50 (quite sustainable), social dimension of 63,47 (quite sustainable) and technological dimension of 38,85 (less sustainable). Multi dimensionally, the index value of 52,63 is obtained, which means that the sheep farming in Galang, Deli Serdang is in a fairly sustainable status.